Shale Oil Occurrence Mechanisms: A Comprehensive Review of the Occurrence State, Occurrence Space, and Movability of Shale Oil - Yangbo Lu; Feng Yang; Ting’an Bai; Bing Han; Yongchao Lu; Han Gao (Energies, 2022)
Shale oil resources are important supplements for the gradually decreasing oil production from conventional reservoirs. Although the exploitation and development of shale oil have achieved considerable progress in the last decade, the commercial extraction of hydrocarbons from shales is still difficult, especially in the lacustrine sedimentary basins of China. One of the key points controlling the successful extraction of hydrocarbons from shale systems is the understanding of the occurrence mechanism of shale oil. This study comprehensively summarizes the theories and techniques to characterize oil occurrence state, occurrence space, oil content, and oil movability in shale systems. Sophisticated instruments, such as high-resolution scanning electron microscopy and high-energy ray imaging, were utilized to qualitatively analyze the pore networks of shales. Advanced physical experiments and numerical simulation techniques, including step-by-step rock pyrolysis, solvent extraction, and NMR, were introduced to characterize shale oil adsorption and movability. By the comparative analysis of the occurrence space, it is found that the image observation technique especially focuses on concentrated pores, such as organic matter-hosted pores. The fluid injection technology yields particular pore size information, which should be calibrated using other information. The 3D digital core, demonstrating the spatial distribution of minerals and pores, is an effective input for shale oil flow simulation. Geological controls analysis about oil retention in organic-rich shales has found that the inorganic matter pores and fractures are probably the “sweet spot” of shale oil, due to the low oil adsorption and high light hydrocarbons content. Many physical experiments measure the total free oil content but neglect the hydrocarbon–rock interaction and the sequential migration of hydrocarbon compounds. Thus, micro-scaled experiments measuring the hydrocarbon adhesion forces are needed to uncover the occurrence mechanism of shale oil in the future.